Meningkatkan Kemampuan Siswa dalam Membaca Puisi dengan Metode Demonstrasi pada Siswa Kelas VI SD Negeri 47/IV Kota Jambi Semester I Tahun Pelajaran 2020/2021 - Dewi Sutria (Universitas Syiah Kuala, 2021)
ABSTRACTThis research is motivated by the inability and lack of interest of students in reading poetry. The formulation of the research problem is whether the demonstration method can improve students' ability to read poetry in fifth grade students of SD Negeri 47/IV Jambi city in the second semester of the 2020/2021 school year? The research aims to improve students' abilities, learning outcomes, and skills in reading poetry, using the Demonstration method in accordance with the correct stages. This research was conducted in July-October 2020, at SD Negeri 47/IV Jambi City. The type of research is classroom action research with 2 cycles consisting of planning, implementation, observation and reflection. Techniques and data collection tools in this study were field notes, list of student scores and student tests. The results of this study indicate that with the Demonstration method, student learning outcomes increase by 53%. It is concluded that the Demonstration method can improve students' ability to read poetry.Keywords: Improving Ability, Reading Poetry, Demonstration